The Modern Arabic Poem from Orality to Interactivity - Elgebily, Salaheldin Abdelaziz (Journal of Arabic Language Sciences and Literature, 2022)
This research deals with the interaction of Arabic poetry with social media, the research begins with an introduction to the poem’s oral style in pre-Islamic poetry, and ending with the interactive poetic text that uses social networks and the Internet to reach the ears of the recipients. The question that the research answers: Is the structure of the poem affected if the means by which the poetic text is transmitted to the reader changes? Would the structure of the poem be different if the poet considers the way the poem will reach the reader? The research here does not attempt to follow a linear historical path. I tried to go back to the beginnings of Arabic poetry when poetry was not written down. Arabic poetry was lyrical and it relied on reciting in forums. The prevailing vision in poetry was based on the poet himself and his unique vision of the universe and life, in contrast to what we know about dramatic and epic poetry in ancient Greek literature. The research suggests that the eras of literature should be divided based on the changes in the poetic structure. With the transition of literature from nomadism to civilization, the poem moves to the stage of codification, and because codification is associated with urbanization, poets can write down their poems for fear of losing them, and that there will be professional narrators of poems. The poem then moved to a stage of complexity, because it did not depend on oral transmission. And when we move to the modern era, the printing machines appear and the poet hides behind. Poetry becomes merely silent letters on white paper. This explains why poets have rebelled against the rhythms of Hebron. When the means changed, poetry structure changed in accordance. With the advent of the Internet, poetry that uses various social networking sites appear. I tried studying the various changes that took place in the poem because of its presence in a new medium, whether it was Facebook, Twitter, Instagram, YouTube, a blog, or a literary magazine published on the Internet.